2020
DOI: 10.31234/osf.io/aez4w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental compression of binary sequences in a language of thought

Abstract: The capacity to store information in working memory strongly depends upon the ability to recode the information in a compressed form. Here, we tested the theory that human adults encode binary sequences of stimuli in memory using a recursive compression algorithm akin to a “language of thought”, and capable of capturing nested patterns of repetitions and alternations. In five experiments, we probed memory for auditory or visual sequences using both subjective and objective measures. We used a sequence violatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 94 publications
(167 reference statements)
0
6
0
Order By: Relevance
“…AB-AABB-AAABBB… = A n B n where n increases sequentially). A possibility, which has received some behavioural support, is that the human brain uses a “language of thought”, including such algebraic patterns, in order to compress deterministic sequences into a regular expression 29,35,7476 . For simplicity, we manipulated here only repeated patterns of various lengths, but found, in line with a possible role of compression, that the barely compressible length-10 pattern AAABAABBAB was more often missed by subjects compared to the other two length-10 patterns, AABABABABB and AAAAABBBBB, which are more compressible ([A 2 , (BA) 2 , B 2 ] and [A 4 , B 4 ] respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AB-AABB-AAABBB… = A n B n where n increases sequentially). A possibility, which has received some behavioural support, is that the human brain uses a “language of thought”, including such algebraic patterns, in order to compress deterministic sequences into a regular expression 29,35,7476 . For simplicity, we manipulated here only repeated patterns of various lengths, but found, in line with a possible role of compression, that the barely compressible length-10 pattern AAABAABBAB was more often missed by subjects compared to the other two length-10 patterns, AABABABABB and AAAAABBBBB, which are more compressible ([A 2 , (BA) 2 , B 2 ] and [A 4 , B 4 ] respectively).…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, we manipulated here only repeated patterns of various lengths, but found, in line with a possible role of compression, that the barely compressible length-10 pattern AAABAABBAB was more often missed by subjects compared to the other two length-10 patterns, AABABABABB and AAAAABBBBB, which are more compressible ([A 2 , (BA) 2 , B 2 ] and [A 4 , B 4 ] respectively). Note, however, that this effect could also result from the difference in the patterns’ apparent statistical bias (which is respectively weak and strong), an alternative we have recently considered and discarded 76 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, very recently, the same formal language of geometry that we tested here was also found to successfully capture the regularities in binary auditory and visual sequences made of only two arbitrary sounds or pictures (Planton et al, 2020). are such codes uniquely developed in human, as postulated by some researchers Fitch, 2014;Hauser et al, 2002), or can they also be observed in non-human primates?…”
Section: Resultsmentioning
confidence: 64%
“…The present research adds further evidence in favor of this framework. Furthermore, very recently, the same formal language of geometry that we tested here was also found to successfully capture the regularities in binary auditory and visual sequences made of only two arbitrary sounds or pictures (Planton et al, 2020). Future research should examine three key open questions.…”
Section: Resultsmentioning
confidence: 78%